The Effects Of Continuous Adaptation Of Online Contents Based On The Aptitude Profile On Learners’ Engagement - Eldenfria, Atef Hamza (2018)
The differences in learning characteristics and preferences among individuals can be attributed to the differences in the formation of the capacity of the mental model that enables the individual to undertake a certain behavior. This mental model is believed to provide the basic logic for individual processing of information. The tendency of this behavior is somehow associated with one’s ability to cognitively engage in the learning process without being distracted by other stimuli. Literature shows that the current mechanisms in adaptive systems do not continuously support the regulation of the complexity of the task in a sequential learning session.